An incentive theory of matching - Alessio J. G. Brown; Christian Merkl; Dennis J. Snower (Kiel Institute for the World Economy (IfW), 2009)
This paper presents a theory explaining the labor market matching process through microeconomic incentives. There are heterogeneous variations in the characteristics of workers and jobs, and firms face adjustment costs in responding to these variations. Matches and separations are described through firms' job offer and firing decisions and workers' job acceptance and quit decisions. This approach obviates the need for a matching function. On this theoretical basis, we argue that the matching function is vulnerable to the Lucas critique. Our calibrated model for the U.S. economy can account for important empirical regularities that the conventional matching model cannot.
Keywords: E24; E32; J63; J64; 330; Matching; incentives; adjustment costs; unemployment; employment; quits; firing; job offers; job acceptance; Arbeitsmarkttheorie; Arbeitsangebot; Arbeitsnachfrage; Ökonomischer Anreiz; Matching; Lucas-Modell; Theorie; USA